SIMILAR BUT DIFFERENT: A TALE OF 2 CASES OF EUGLYCEMIC DIABETIC KETOACIDOSIS - Chiew, KS; Nurazni, RA Raja; Zakaria, MH (Journal of the ASEAN Federation of Endocrine Societies, 2021)
INTRODUCTION Euglycemic diabetic ketoacidosis (euDKA) is a subset of diabetic ketoacidosis (DKA) with increased anion gap metabolic acidosis and ketosis but normal or minimally elevated blood glucose. Notorious in the recent years due to its association with the increasingly popular sodiumglucose cotransporter 2 (SGLT2) inhibitors, euDKA may also be caused by other conditions. Here, we describe 2 cases of euDKA of different etiologies. RESULTS The first case is a 41-year-old female with poorly controlled type 2 diabetes mellitus (HbA1c 12.5%) who was on metformin and empagliflozin. She had discontinued her insulin glargine/lixisenatide injections after missing her follow-up in April 2020 due to the COVID-19 pandemic. In September 2020, she presented with 4 days of abdominal pain and persistent vomiting. She had severe metabolic acidosis (pH 6.9 and HCO3 1.4 mEq/L) with a random capillary blood glucose of 9 mmol/L. Despite fluid resuscitation, sodium bicarbonate infusion and continuous veno-venous hemofiltration (CVVH), her metabolic acidosis persisted for the next 4 days. Her serum ketone was then noted to be elevated (6.4 mmol/L). She was diagnosed with euDKA and after treatment with intravenous insulin and dextrose, it resolved. The second case is a 33-year-old female with type 1 diabetes mellitus who has had 4 prior episodes of DKA since her diagnosis in 2013. She was pregnant at 31 weeks when she presented with 2 days of poor oral intake, epigastric discomfort and vomiting. Her capillary blood glucose was 9.2 mmol/L with severe metabolic acidosis (pH 7.1 and HCO3 5.7 mEq/L) and ketosis (serum ketone was 5.1 mmol). She was diagnosed with euDKA which resolved after 16 hours of intravenous insulin and dextrose. CONCLUSION Aside from SGLT2 inhibitors, euDKA is also associated with other conditions such as pregnancy. High index of suspicion in normoglycemic patients is required to avoid delay in diagnosis and management.